IMPLICATIONS OF IMPLEMENTING THE E-PERFOMANCE APPLICATION FOR EMPLOYEE PERFORMANCE ASSESSMENT AT THE CUSTOMS AND EXCISE SUPERVISION AND SERVICE OFFICE (KPPBC) MADYA CUSTOMS TYPE JUANDA SURABAYA - Tarmuji, Muhammad Anton; Kuswandi, Kuswandi; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2024)
The E-Performance system is a cutting-edge digital platform created to streamline performance evaluations for government employees, in accordance with the regulations set forth in ASN Law Number 5 of 2014. This research delves into the effects of the E-Performance software on the performance of staff members at the Customs and Excise Supervision and Services Office (KPPBC) of Madya Juanda Type Customs and Excise, located in Surabaya. Through the use of descriptive qualitative techniques, information was gathered via purposive sampling, interviews, observations, and document scrutiny. The results suggest that both KPPBC TMP Juanda and its workforce are well-equipped to reach and sustain high levels of performance, by aligning personal objectives with organizational goals and nurturing a culture of excellence. The performance evaluation system has proven to be successful in enhancing accountability within the public sector. Nevertheless, in order to uphold staff motivation, performance agreements should be set realistically to prevent any deviation from expected behavior and a decrease in performance standards. It is advisable to conduct regular counseling sessions to promptly identify and address any concerns, thereby ensuring continuous motivation and optimal performance.